Chlamydia trachomatis and human papillomavirus 16 and 18 in adolescents - Vrtačnik-Bokal, Eda (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
Adolescents represent a risk group for sexually transmitted infections. The aim of this study was to find the prevalence of Chlamydia trachomatis (CT) andhuman papillomavirus (HPV) in adolescents. Additionally, we wanted to know,whether the prevalence of CT was so high that antibiotic prophylaxis would be appropriate before termination of pregnancy. In the study we enrolled200 adolescents: 100 came for termination of pregnancy and 100 for a contraceptive method. CT was isolated in 6% in the first and in 4% in the second group. HPV was positive in 26% in the first and in 13% in the second group (p<0.05). A 6% prevalence of CT justifies the use of antibiotic prophylaxis before termination of pregnancy.
Keywords: Adolescenca; Adolescence; Antibiotic Prophylaxis; Antibiotična zaščita; Chlamydia Infections; Chlamydia Trachomatis; Epidemiology; Klamidijske infekcije; Papillomavirus, Human; Papilomavirus človeški; Prevalenca; Prevalence; Sex Behavior; Spolno vedenje